High Density Multi-Channel Passively Aligned Optical Probe for Testing of Photonic Integrated Circuits - Xaveer Leijtens; Rui Santos; Kevin Williams (IEEE Photonics Journal, 2021)
In this work we report the results of high density multi-channel optical multiprobes with pitches of 25 ${μ }\rm{m}$ and 50 ${μ }\rm{m}$ that provide edge-coupling used for on-wafer parallel testing of photonic integrated circuits. The probes are fabricated in an oxynitride platform and test demonstrations were carried out of edge-coupled indium-phosphide based photonic integrated circuits (PICs). Thirty-two optical parallel connections are simultaneously, passively aligned between the probe and the PIC by means of integrated guiding channels. The initial placement tolerance is more than 4 ${μ }\rm{m}$ to give a passive alignment with an optical power variation of less than 1 dB. Multi-port loop-back optical power measurements are reported and the wavelength-dependent net modal gain of integrated semiconductor optical amplifiers was measured to further validate the concept.